Trends of Healthy Life Expectancy of the Elderly in China in 1994–2015: Revisiting From the Perspective of Morbidity Transition - Zhang, Zhen; Dong, Junhan; Zhao, Chenyuan; Li, Qiang (Frontiers in Public Health, 2022)
Research on healthy life expectancy (HLE) in China has been fueled by a spate of new data sources and studies, yet no consensus is reached on the pattern of HLE changes and the underlying mechanism. This study examined the change of HLE in China over 20 years with long term national data. Health status, measured by activities of daily living, is combined with mortality to calculate the disability-free life expectancy by the Sullivan method. The results show that the HLE rose slower than life expectancy (LE) in 1994-2004, suggesting morbidity expansion. In 2010-2015, the proportion of HLE to LE continuously declined but at a decreased rate compared to the 1994-2004 period, indicating a sign of the faltering of morbidity expansion. Importantly, a counterfactual analysis shows that health improvement has been increasingly important in increasing HLE over 1994-2015, despite the importance of mortality decline. As with the difficulty of further reducing old-age mortality, the increase in HLE will increasingly rely on health improvement, probably leading to morbidity compression or dynamic equilibrium. Whether and how such a transition is unfolding in the future remains open and need further research.